Bahasa Tulis Pada Anak Kelas 1 SD Negeri 006 Pelita dengan Gangguan Disleksia (Kajian Psikolingusitik) - Nur Raudhoturrahmah; Vira Shafina; Pajriansyah Pajriansyah; Fatmawati Fatmawati (UIR Press, 2023)
Dyslexia is a type of language disorder that can hinder children's language development. Dyslexia affects the brain's neurological function, which functions in language processing. Dyslexia also affects children's writing ability. The purpose of this research is to describe and explain the forms of written language in dyslexic children. This research uses a qualitative descriptive research type. The subject of this research is Fatir who is a first grade elementary school student. The material for this study comes from the documentation of the forms of written and spoken language studied. This research data collection technique through interviews, documentation and observation. The research material was analyzed through material reduction, presentation, conclusion and material review, and the results of this study were that dyslexia causes multiple disorders in the form of children's written language. These errors include writing letters upside down, skipping letters, adding letters, and replacing letters that don't match. Fatir's reverse letter is different from other dyslexic children. The letters that are often spelled backwards are b, d, k, e, a, r, h, s, p and t. Even though Fatir has a weakness in writing, he excels in listening.